Is there a place for nature conservation in the Transkei? - M.M. Ntloko (Koedoe: African Protected Area Conservation and Science, 1977)
The Republic of the Transkei is situated in the south-east of the Republic of South Africa and is bounded by the Cape Province, Natal, Lesotho and the Indian Ocean. The area of the country is some 43 200 km2, almost as large as Denmark and twice the size of Wales. It is a country made up of mountainous regions along the Lesotho border and the rest is made up mostly of rolling hills with deep river valleys. It is a summer rainfall region ranging between 500 mm and 1300 mm per year and thus the country may be termed well watered. Climatic conditions may be described as temperate with occasional frosts during the worst winter months.